Interlimb Differences in Control of Movement Extent - Sainburg, Robert L. (2004)
The current study was designed to examine potential interlimb asymmetries in controlling movement extent. Subjects made repetitive single-joint elbow extension movements while the arm was supported on a horizontal, frictionless, air-jet system. Four targets of 10, 20, 35, and 45° excursions were randomly presented over the course of 150 trials. For both arms, peak tangential hand velocity scaled linearly with movement distance. There was no significant difference between either peak velocities or movement accuracies for the two arms. However, the mechanisms responsible for achieving these velocities and extents were quite distinct for each arm. For the dominant arm, peak tangential finger acceleration varied systematically with movement distance. In contrast, nondominant-arm peak tangential acceleration varied little across targets and, as such, was a poor predictor of movement distance. Instead the velocities of the nondominant arm were determined primarily by variation in the duration of the initial acceleration impulse, which corresponds to the time of peak velocity. These different strategies reflect previously identified mechanisms in controlling movement distance: pulse-height control and pulse-width control. The former is characterized by a variation in peak acceleration and has been associated with preplanning mechanisms. The latter occurs after peak acceleration and has been shown to depend on peripheral sensory feedback. Our findings indicate that the dominant-arm system controls movement extent largely through planning mechanisms that specify pulse-height control, whereas the nondominant system does so largely through feedback mediated pulse-width control.